PELATIHAN KETERAMPILAN KONSELING PASTORAL DASAR BAGI GURU SEKOLAH MINGGU DI WILAYAH LABUHAN BATU SELATAN - Sahat Tua; Ezra Senita Ambarita; Martha Samuell Kristina (PUAN INDONESIA, 2026)
This community service program aims to enhance the capacity of Sunday School teachers in providing faith-based accompaniment for children and families through basic pastoral counseling training in Labuhan Batu Selatan. The program is grounded in the limited preparedness of Sunday School teachers in addressing increasingly complex emotional, social, and spiritual issues faced by children. A participatory-reflective training approach was employed, including interactive lectures, group discussions, case studies, simulations, and reflective sessions. The results indicate an improvement in participants’ understanding of their role as faith companions rather than professional counselors, as well as strengthened skills in empathetic communication, active listening, and ethical role awareness. The training also fostered greater contextual sensitivity toward children’s and families’ life situations. It is concluded that this program effectively contributes to improving the quality of faith accompaniment for children and families and is highly relevant to grassroots church ministry needs.